Meningkatkan Pengetahuan Masyarakat mengenai Pelecehan Seksual melalui Webinar Interaktif - Farisandy, Ellyana Dwi (Journal Pemberdayaan Masyarakat Indonesia, 2023)
Cases of sexual harassment have increased from year to year. The researcher collaborates with Lentera Muda Indonesia Community to develop a community service program in the form of psychoeducation. This psychoeducation aims to increase knowledge about sexual harassment. The participants of this activity are Indonesian people, totaling 44 participants. The results of this activity can be seen in the reactions where participants are active and enthusiastic in participating in the activity from the beginning to the end of the activity. The researcher hopes that this activity can also be implemented in various contexts and different settings.